1980
DOI: 10.1149/1.2129792
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics and Polymorphism of Chemically Deposited CdS Films

Abstract: The kinetics of growth for chemical deposition of normalCdS films from alkaline solutions of cadmium salts has been studied with respect to temperature of deposition and the relative concentrations of the various reactants in the solution. It has been established that the growth of the film takes place either by ion‐by‐ion condensation of Cd+2 and S−2 ions or by adsorption of colloidal particles of normalCdS formed in the solution, depending on the various deposition parameters and the method of preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(157 citation statements)
references
References 0 publications
7
150
0
Order By: Relevance
“…However, several authors have reported explicitly or implicitly that the lower the reaction temperature the lower the thin film growth rate [12,15,20,21,23,28,34,35,54,[77][78][79][80][81]84,87,90,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. Thus, without delving into the cases in which homogeneous precipitation is favored, which limits the maximum d-a limit which was directly reported [12,15,21] or simply evident in the results reported [115,118,120] by some authors-the use of low temperatures lengthens the time required to achieve a thin film with determined d compared to the time required at higher temperatures. For example, Figure 5 shows the log(T -1 ) value at 400 nm of the CdS thin films synthesized by using the economical formulation at different temperatures and different immersion times, and it confirms the increase in thin film growth rate with increasing temperature.…”
Section: Selection Of a Convenient Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, several authors have reported explicitly or implicitly that the lower the reaction temperature the lower the thin film growth rate [12,15,20,21,23,28,34,35,54,[77][78][79][80][81]84,87,90,[103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. Thus, without delving into the cases in which homogeneous precipitation is favored, which limits the maximum d-a limit which was directly reported [12,15,21] or simply evident in the results reported [115,118,120] by some authors-the use of low temperatures lengthens the time required to achieve a thin film with determined d compared to the time required at higher temperatures. For example, Figure 5 shows the log(T -1 ) value at 400 nm of the CdS thin films synthesized by using the economical formulation at different temperatures and different immersion times, and it confirms the increase in thin film growth rate with increasing temperature.…”
Section: Selection Of a Convenient Temperaturementioning
confidence: 99%
“…Mainly for the economical reason, from this point on we will refer to it as economical formulation-although this can be further enhanced-whose specifications are depicted in Table 3. These specifications can be changed-usually a variation in the Cd 2+ concentration is done-but it is necessary to take into account that the deposition conditions, like the pH of the On the other hand, although different authors have included in their reports studies in which the reaction temperature is varied [12,15,[20][21][22][23][24]27,28,34,35,54,73,[77][78][79][80][81]84,85,87,89,90,, there is no report about the energy consumption of the equipment that keeps constant the temperature of the water bath at a selected value. For this purpose, we measured the energy consumption during the first minutes when a temperature of 30˚C, 50˚C, and 70˚C is achieved, starting from a water bath at 25˚C.…”
Section: Selection Of a Convenient Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the cases with high ammonia and high stir rates,the wurtzite structure of CdS was observed. In the same cases with no stir the more common zinc blende cubic CdS was observed [62]. It is assumed that the stirring prevented formation of clusters hence limited the sticking of the colloidal particles from the solution and limiting the formation of the zinc blende.…”
Section: Effects Of Substrates and Stirringmentioning
confidence: 96%
“…In general the most noticeable effect of non-stirring is the loose adherence of the film to the substrate [62]. This can be explained by the non-dissolution of the clusters in the solution.…”
Section: Effects Of Substrates and Stirringmentioning
confidence: 99%